Charge Balance in Red QLEDs for High Efficiency and Stability via Ionic Liquid Doping. (20th May 2022) - Li, Yunfei; Fan, Xi; Shen, Cai; Shi, Xixiu; Li, Pengcheng; Hui, Kwun Nam; Fan, Junpeng; Kang, Kai; Zhang, Ting; Qian, Lei
Abstract: Colloidal quantum dot light‐emitting diodes (QLEDs) simultaneously exhibiting high external quantum efficiency (EQE) and operation stability are achieved via a simple solution processing. A silver bis(trifluoromethane‐sulfonyl)imide treatment that is used to chemically dope the poly(3, 4‐ethylenedioxythiophene):poly(4‐styrenesulfonate) (PEDOT:PSS) hole injection layer (HIL) is proposed. The ionic liquid salt acts as an effective p ‐dopant for high charge concentrations; and it raises the work functions and surface potentials of the PEDOT:PSS HIL for an interface energy band alignment. Benefiting from a raised hole mobility and a better charge mobility balance, the processing‐simple colloidal red QLEDs yielded the highest EQE of up to 17.4%. In particular, a very broad plateau of EQE values over 16.5% in the brightness of 400–10 000 cd m −2 is obtained. Moreover, the packaged QLEDs exhibit an excellent operation stability in ambient air. The T95 (time for the device brightness to decrease to 95% of its initial brightness) at an initial brightness of 1000 cd m −2 is 4160 h. The work highlights a promising ionic liquid strategy to guide the development of high‐performance and cost‐effective QLEDs. Abstract : A high‐performance CdSe/ZnS colloidal quantum dot light emitting diode (QLED) made from PEDOT:PSS hole injection layers is demonstrated. Via an ionic liquid treatment, the colloidal QLEDs exhibited the highest external quantum efficiency as high as 17.4% with a broad plateau; and the devices showed outstanding stability with T95 of 4160 hours at an initial brightness of 1000 cd m −2 in ambient air.